Empirical Formula for Estimation the Sediment Load in Shat AL-Gharaf River - Maatooq, Jaafar .S .; Omran, Hassan. A.; Aliwe, Haleem K. (Basrah Journal for Engineering Sciences, 2016)
In this research ,the sediment load in Shat Al- Gharaf River , lies in the south of Iraq ,has been studied . Two empirical formulas those have been presented by ; Bagnold and Van Rijin were adopted as a deterministic equations for computing the sediment discharge in selected reaches of river . The application of these equations requires to do different hydraulic , sediment , and geometric measurements for the selected reaches . Accordingly , thirteen sections along the river within a study area have been adopted . After analyzing the available data , a new formula for estimating the suspended sediment load in Shat Al-Gharaf was developed , depending on the data for ten sections of this river and by using SPSS program , the determination coefficient of the new formula was (R 2 =0.94) . The validity of the established formula has been verified using some well related (i.e., nearly the same hydraulics and geometrical circumstances) of field data over the world was selected from published literatures [8] these are : Colorado river data of the U.S.B.R.(1958) ,River data from Leopold (1969) , and India canal data of Chaudry et.al.(1970). As well as ,those observed in the remaining three sections of present river , the verification shows a good agreement . The results of the adopted two formulas and the new formula were compared with field measurements using Discrepancy Ratio (bais) method . The suggested new formula gave the best results where 50% of data located within a discrepancy ratio close to one and 30% of data located within an error ±20% , that is refer to suitability adoption this formula as a deterministic equation to estimate the sediment load in Shat Al-Garaf river within a study reach .